Evaluating medium chain fatty acids as a replacement for antibiotics or zinc oxide in nursery pig diets - Breault, Madison T.; Lerner, Anne B.; Jones, Cassandra K. (My University, 2019)
Increased pressure from pork consumers to reduce the use of antibiotics and ZnO in diets of nursery pigs creates a need for research regarding antibiotic alternatives. The objective of this study was to compare the effects of different diets on growth performance of pigs over a 35d period. A total of 360 pigs (200x400 5.4 ±0.06 kg BW) were assigned to 6 treatment diets in 2 phases, then a common diet for the third phase. The treatments included: 1) negative control; 2) ZnO (3,000ppm in phase 1 and 1,500ppm in phase 2); 3) 50g/ton carbadox; 4) 1%C6:C8:C10 MCFA; 5) 1%R2 (Feed Energy, Des Moines, Iowa); or 6) 1%FORMI GML (ADDCON; Bitterfield-Wolfen, Germany). The experiment used a randomized design with pen being the experimental unit consisting of 6 pigs/pen and 10 replicates. Pigs were weighed and feed intake was recorded weekly to calculate ADG, G:F, and ADFI. Data was analyzed using PROC GLIMMIX (SAS version 9.4; Cary, NC). Responses showed that from d0 to 19 pigs fed ZnO, carbadox, and 1%FORMI had increased ADG (P<0.05) while other treatments were intermediate. Pigs fed ZnO had improved ADFI (P=0.004) compared to those fed R2, negative control, and C6:C8:C10 diets with other diets being intermediate. Overall, G:F was not different among treatments (P=0.078). For the overall study (d0 to 35) ZnO and carbadox resulted in improved ADG(P=0.012) with the others being intermediate. The results of the study concluded that ZnO and carbadox are effective options for growth and that 1%FORMI MCFA can potentially be used as an alternative for carbadox or ZnO with minimal effects on growth. Additional research should be performed to further evaluate this topic.
Keywords: Spring 2019